KORELASI STATUS GRAVIDA DENGAN PRE EKLAMPSIA DI KABUPATEN BANYUMAS - Suryandari, Artathi Eka; Trisnawati, Yuli (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2019)
Pre eclampsia is a unique disorder found only in pregnancy period. Since long ago pre eclampsia has been described as a disease characterized by classic trias symptoms, namely hypertension, proteinuria and edema in pregnant women. However, this preeclampsia is actually a manifestation of various clinical signs and symptoms that accompany microvascular changes in various organs of a pregnant woman. The purpose of this study was to determine the relationship between gravida status and pre-ecalmpsia. This research is a descriptive study with a case control approach. The data used in the form of primary data, data collection using a questionnaire. The population in this study were all pregnant women in Banyumas district. The sample in this study was purposed sampling with 30 respondents with pre-eclampsia as the case and 30 respondents with normal pregnancy as controls. Data analysis using the chi square test. The results of the study Most of the respondents were multigravida (75%) and there was no relationship between gravida status and the prevalence of Ï = 0.371Keywords: gravida status, pre eclampsia